Identification of the gene encoding 3-(5-oxo-2-thioxoimidazolidin-4-yl) propionic acid desulfhydrase in Burkholderia sp. HME13. Issue 3 (31st December 2020) - Muramatsu, Hisashi; Maguchi, Hiroki; Harada, Taisuke; Kashiwagi, Takehiro; Kim, Chul-Sa; Kato, Shin-ichiro; Nagata, Shinji
ABSTRACT: Here, we report the identification of the gene encoding a novel enzyme, 3-(5-oxo-2-thioxoimidazolidin-4-yl) propionic acid desulfhydrase, in Burkholderia sp. HME13. The enzyme converts 3-(5-oxo-2-thioxoimidazolidin-4-yl) propionic acid and H2 O to 3-(2, 5-dioxoimidazolidin-4-yl) propionic acid and H2 S. Amino acid sequence analysis of the enzyme indicates that it belongs to the DUF917 protein family, which consists of proteins of unknown function.